LIVE STREAMING, TRUST, AND RISK PERCEPTION: DETERMINING FACTORS FOR STUDENT PURCHASING DECISIONS THROUGH SHOPEE - Odika Syifa’un Nisa; Lativa Hartiningtyas (Jurnal Cakrawala Ilmiah, 2026)
This research is based on the rapid development of information technology in the digital era in the economic sector, especially in online shopping activities through e-commerce such as Shopee. The live streaming feature is increasingly popular with e-commerce business people as a promotional medium. The level of trust and risk perception are important factors that affect consumers' purchasing decisions because online transactions have many concerns such as uncertainty of product quality and security in transactions. The purpose of this study is to test the influence of live streaming, trust and risk perception on student purchase decisions through Shopee, to test the influence of live streaming on student purchase decisions through Shopee, to test the influence of trust on student purchase decisions through Shopee, to test the influence of risk perception on student purchase decisions through Shopee. This study uses a quantitative approach with an associative type. The sampling technique in this study uses a probability sampling technique with a proportionate stratified random sampling method with a sample of 92 respondents, namely FEBI UIN Sayyid Ali Rahmatullah Tulungagung students class of 2021. The data analysis method uses multiple linear regression. The results of the study show that live streaming variables, trust and risk perception simultaneously affect students' purchasing decisions through Shopee. The variables of live streaming and partial trust have a positive and significant effect on student purchase decisions through Shopee. The risk perception variable did not have a significant effect on students' purchasing decisions through Shopee.